2019
DOI: 10.1021/acsnano.8b04047
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Compound Eyes Prepared by a Combination of Air-Assisted Deformation, Modified Laser Swelling, and Controlled Crystal Growth

Abstract: This study presents the manufacturing process of bioinspired compound (BIC) eyes. The hierarchical eyes were accomplished by a combination of (i) modified laser swelling, (ii) air-assisted deformation, and (iii) controlled crystal growth. The results show that the addition of nanostructures on the surface effectively improved the water repellent performance with a contact angle (CA) of ∼160° and generally decreased the reflection by ∼25% in the wavelength range of 400–800 nm than the planar surface. Apart from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 53 publications
1
59
1
Order By: Relevance
“…4f. According to the analyses of previous research [15,36], denser nanolenses increase the surface roughness of the PDMS film, which results in the enhanced hydrophobic performance of the surface. The WCAs of the surface of the PDMS films increase with increasing densities of nanolenses (determined by the distances D1-D4).…”
Section: Characterization Of the Waterproof Ability Of The Artificialmentioning
confidence: 93%
See 1 more Smart Citation
“…4f. According to the analyses of previous research [15,36], denser nanolenses increase the surface roughness of the PDMS film, which results in the enhanced hydrophobic performance of the surface. The WCAs of the surface of the PDMS films increase with increasing densities of nanolenses (determined by the distances D1-D4).…”
Section: Characterization Of the Waterproof Ability Of The Artificialmentioning
confidence: 93%
“…However, the high cost and time required for the complicated 3D fabrication process limit its fabrication efficiency for widespread applications. On the other hand, based on the planar MLAs manufactured via conventional methods, artificial compound eyes can be fabricated indirectly by deforming planar MLAs to curved MLAs using vacuum absorption and thermoplastic molding [15][16][17]. The deformation of MLAs film is a simple and efficient method for fabricating artificial compound eyes.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced from Li M. et al ( 2019a ) with the permission of the WILEY-VCH. Reproduced from Bian et al ( 2020 ) with the permission of Bian et al Reproduced from Raut et al ( 2015 ) and Li J. et al ( 2019 ) with the permission of the American Chemical Society. Reproduced from Li M. et al ( 2019b ) with the permission of Li et al…”
Section: Fabrication Of Superwetting Mlasmentioning
confidence: 99%
“…Superwetting structures can also be directly created on the top surface of the microlenses, allowing the whole MLA surface to be decorated with a layer of superwetting structures. Li J. et al ( 2019 ) reported a novel manufacturing strategy to prepare superhydrophobic MLA and ACE. A concave MLA was firstly achieved on the elastomer substrate by a template replication.…”
Section: Fabrication Of Superwetting Mlasmentioning
confidence: 99%
“…The femtosecond laser has ultra-high peak power and ultra-short reaction time, which not only will realize high removal rate of polymer materials, but also ensure the smoothing of the prepared micro-nano structure. Furthermore, the femtosecond laser can be used to process flexible, repeatable, precise, and controllable microstructures on the surface of a variety of materials including polymers [19][20][21][22]. The Wenzel model [23] and Cassie-Baxter model [24] were proposed to predict the contact angle for all the micro/nano structures.…”
Section: Introductionmentioning
confidence: 99%